Institutionalizing Education within Mosques: A Model for Islamic Community Development and Social Well-being in Kelantan - Razak, Ateerah Abdul; Mustafa, Nor Hanim; Musa, Nik Yusri; Ahmad, Mohd Kamil (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Mosques have historically functioned not only as places of worship but also as key institutions for education, social cohesion, and community development within Islamic societies. In Kelantan, Malaysia, this multidimensional role has been institutionalised through the set of guidelines Garis Panduan Kewujudan Institusi Pendidikan dalam Kawasan Masjid (The Integration of Educational Institutions within Mosque Environments) issued by the Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) - Council of Islamic Religion and Malay Customs. This study investigates the institutional integration of educational facilities within mosque compounds, positioning it as a model for Islamic community advancement and social well-being. The guideline addresses governance, waqf land management, financial sustainability, educational programming, community engagement, and security protocols, underpinned by Islamic principles and indigenous cultural norms. Through document analysis of the MAIK guideline, this paper identifies key mechanisms that harmonise religious, educational, and socio-cultural objectives, contributing to the preservation of cultural identity and the strengthening of community resilience. Findings suggest that mosque-based educational institutions in Kelantan act as transformative platforms that foster moral development, social harmony, and collective welfare. This model demonstrates the applicability of Islamic and indigenous psychological frameworks in shaping sustainable, faith-based community development strategies. The Kelantan experience offers valuable insights for Muslim communities seeking to reinforce social infrastructure and holistic empowerment through religiously grounded educational systems. This paper further contributes to discourses on Islamic and Indigenous Psychology by positioning the mosque as a central institution for integrated community empowerment.